Effects of insulin combined with metformin on serum cystatin C, homocysteine and maternal and neonatal outcomes in pregnant women with gestational diabetes mellitus - Zheng, Jizeng (Exp Ther Med, 2020)
Effects of insulin combined with metformin on serum cystatin C (Cys C), homocysteine (Hcy) and maternal and neonatal outcomes in pregnant women with gestational diabetes mellitus (GDM) were investigated. In total, 80 cases of pregnant women diagnosed with GDM in the Department of Obstetrics and Gynecology of Liaocheng Third People's Hospital from July 2015 to July 2017 were selected and divided into a study group (42 cases) and a control group (38 cases). The study group was treated with insulin combined with metformin, and the control group was treated with insulin. Fasting blood glucose (FBG) and postprandial blood glucose after 2 h (2hPG) of the two groups were compared before and after treatment. Levels of serum Cys C, Hcy, urinary protein (UmAlb), postpartum maternal outcomes and adverse reactions during pregnancy were compared in the two groups before and after treatment. After treatment, the level of FBG and 2hPG in the control group was higher than that in the treatment group (P<0.05). After treatment, the level of serum Cys C and Hcy in both groups were lower than that before the treatment, and the level in the study group was lower than that in the control group (P<0.05). The total incidence of neonatal adverse outcomes and the number of adverse pregnancies in GDM patients in the study group were significantly lower than those in the control group (P<0.05). There were no significant differences in adverse reactions during pregnancy between the two groups (P>0.05). In conclusion, insulin combined with metformin is more effective than insulin alone in reducing serum Cys C and Hcy levels, with significant effect on the improvement of maternal and neonatal outcomes.